Exploring the Advantages of English Club in Improving Speaking Skill at Columbia Nursing Academy Year 2022/2023 - Madina; Sidabutar, Lita Imanuela (Asian Journal of Applied Education (AJAE), 2024)
The courage of students in honing their speaking skills to become confident with English club activities such as in this study. "Speaking ability of columbia Nursing Academic Students" in Medan City District, North Sumatra Province is the subject of this research. The research method used is data collection such as filling out questionnaires and observation. The type of research used is qualitative research. This study also aims to prove that the activities of the English club can generate confidence to train students' speaking skills. Based on the lack of confidence of Columbia nursing academic students in speaking English, the researchers conducted English club activities to foster students' confidence in honing their English speaking skills.